Strategi Humas Bandara I Gusti Ngurah Rai dalam Menangani Kesalahan Penulisan Nama Maskapai pada Press Releases - Elina Fransiska (CV. ITTC INDONESIA, 2026)
This study examines how the Public Relations (PR) unit of I Gusti Ngurah Rai International Airport managed a written message error in an official press release, specifically the incorrect naming of an airline that had already been published by multiple media outlets. The study purpose was to analyze PR strategies in correcting the error, the construction of corrective discourse, and the dynamics of PR–media relations in post-publication correction. Using a qualitative approach, this study applies discourse analysis to the original press release and subsequent corrective communications with media organizations, guided by the four-step PR process model of Cutlip, Center, and Broom. The findings show that the PR unit identified the problem following direct notification from the affected airline, planned corrective actions by mapping media coverage, and implemented targeted communication through individualized clarification requests rather than public apologies. However, variations in media responses revealed structural constraints related to editorial autonomy. The study concludes that typographical errors in official PR communications should be understood as organizational communication failures with potential reputational implications. Effective management requires integrated message control, proactive media relations, and systematic evaluation to prevent recurrence and strengthen institutional credibility.